Neurologic Outcome of Infantile Hypoglycemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The neurologic development of 90 patients with persistent hyperinsulinemic hypoglycemia was studied retrospectively at Hospitalier Universitaire Necker-Enfants Malades, Paris, France.